Pragmatic and hedonic aspects of user experience in Virtual Reality: analysis of novice users’ information mediation during their first interaction with a Metaverse platform - Baptista Oliveira Souza, Lucas; Celeste Santana Cunha, Aura; Monteiro Xavier de Lima, Mariana; Enéas Peres Ricca, Diego (InfoDesign, 2023)
The topic of virtual and extended reality has increasingly captured the interest of developers who aim to widely adopt it among the general population. Over the last five years, significant investments in this field have brought the term “Metaverse” back into discussions as a potential ideal for social interaction within virtual environments. This paper aims to contextualize the Metaverse and its potentialities by investigating its relation to new users from a UX (user experience) design perspective. This work aims to understand the pragmatic and hedonic aspects of user experience and information mediation of novice users during their first interaction with a Metaverse application. To achieve this, we selected six users and analyzed their first interactions within the popular digital platform called “VRchat”. For data analysis, we used a method inspired by Marc Hassenzahl’s AttrakDiff tool and investigated the interactions based on three main aspects: interactivity, immersion, and self-identification. As a result, we noticed a positive impression of virtual reality (VR) on user experience after immersion. We also observed some UI (user interface) solutions that are functional, and others that are not, in an immersive interface. Based on these findings, we propose some hypotheses for solution paths to enhance these three aspects of the Metaverse experience.